"This Heavy Thing": Catherine the Great's Coronation Crown. Issue 2 (4th May 2019) - Jaques, Susan
Abstract: After seizing power in 1762, Catherine II organized the most extravagant coronation money could buy. To add to the splendour, she placed a rush order for a crown. With carte blanche to use luxurious objects from the Russian treasury, jeweler Jérémie Pauzié designed "one of the richest objects that has ever existed in Europe". Five thousand diamonds adorned the surface of the two half spheres; two rows of white pearls outlined the edges of the miters. The pièce de résistance was a nearly 400-carat ruby red spinel, removed from the crown of Empress Anna, niece of Peter the Great. The world's second largest spinel had been acquired in Peking in 1676 by Russia's envoy to China. Thrilled, Catherine declared that she'd somehow manage to hold "this heavy thing" on her head during the four-hour Kremlin ceremony. In the tradition of Byzantine emperors before and Napoleon after, Catherine placed the crown on her own head. It was worn by all of her successors, from her son Paul I to Nicholas II, Russia's last tsar.